Self-assembled naphthalimide derivatives as an efficient and low-cost electron extraction layer for n-i-p perovskite solar cells. Issue 88 (17th October 2019) - Li, Lingchang; Wu, Yongzhen; Li, Erpeng; Shen, Chao; Zhang, Hao; Xu, Xiaojia; Wu, Gao; Cai, Molang; Zhu, Wei-Hong
Abstract : We demonstrate self-assembled naphthalimide derivatives as an efficient electron extraction contact for n-i-p structured perovskite solar cells. Abstract : Based on self-assembly, novel electron extraction layers (EELs) composed of naphthalimide (NPI) derivatives are constructed for application in n-i-p perovskite solar cells. Upon molecular energy level modulation, the power conversion efficiencies have been largely improved from 5.4% to 16%. Such low-cost and highly regulable EELs are promising for future commercial applications.